Ionic liquid functionalized β-cyclodextrin modified electrode as electrochemical sensor for 2,4-dichlorophenol / Fairuz Liyana Mohd Rasdi - Fairuz Liyana , Mohd Rasdi (2020)
This thesis described the synthesis and characterization of ionic liquid monofunctionalized β-cyclodextrin (β-CD-1-BIMOTs) and ionic liquid difunctionalized β-cyclodextrin (β-CD-2-BIMOTs) for sensor applications. The physical characterizations of these compounds have been conducted using nuclear magnetic resonance (NMR), Fourier transform infra-red (FTIR), energy dispersive x-ray (EDX), x-ray diffraction (XRD) and Brunauer-Emmet-Teller (BET) analyses. These compounds were used as modifiers for carbon paste electrode (CPE). Cyclic voltammetry and chrono-amperometry methods were employed to examine the electrochemical responses of all prepared CPEs. All prepared electrodes show responses towards the target analyte of 2,4-dichlorophenol (2,4-DCP). Both β-CD-1-BIMOTs/CPE and β-CD-2-BIMOTs/CPE give higher current (i) responses compared to β-CD/CPE and native CPE. The optimum potential value for the oxidation of 2,4-DCP was decreased with the increase of IL substitution on β-CD which was from 0.75 V (β-CD-1-BIMOTs/CPE) to 0.68 V (β-CD-2-BIMOTs/CPE). Under the systematic optimized and validated conditions, the i response and the concentration of 2,4-DCP had a good linear relationship in the range of (4.3 – 100) ×10-6 mol L-1 and (13.8 – 100) × 10-6 mol L-1; respectively for β-CD-1-BIMOTs/CPE and β-CD-2-BIMOTs/CPE. Both sensors were successfully applied for the determination of 2,4-DCP in leachates from landfill, mineral water and lake water with the recovery of 85.5% - 117.7%. From the interference study, β-CD-2-BIMOTs/CPE was unable to differentiate the response between 2,4-DCP and its analogues where the change of signals >5% in comparison to β-CD-1-BIMOTs/CPE. The possible interaction geometries of the β-CD-1-BIMOTs-2,4-DCP and β-CD-2-BIMOTs-2,4-DCP were proposed to investigate the significant differences in the oxidation potential values and the selectivity properties between both sensors through spectroscopic techniques (NMR and ultraviolet-visible (UV-Vis)).